2022
DOI: 10.1097/acm.0000000000004904
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Professional Identity Formation Interventions in Medical Education

Abstract: Purpose Professional identity formation (PIF) can be defined as the integration of the knowledge, skills, values, and behaviors of a profession with one’s preexisting identity and values. Several different, and sometimes conflicting, conceptualizations and theories about PIF populate the literature; applying these different theories in PIF curricula and pedagogic strategies can profoundly impact the PIF of future physicians. The authors conducted a critical review of the recent literature on PIF interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 105 publications
0
25
0
Order By: Relevance
“…professional or minoritised groups), we necessarily only capture part of the story. Indeed, there is an increasing chorus of researchers critiquing the lack of diversity reflected in the ‘data’ on professional identities (historically comprising of White, male and medical cultures) and the need for a critical perspective from researchers 2,14,15,17 . One of these absent groups comprises mental health professionals, specifically clinical psychologists, which are the focus of this article.…”
Section: Reviews Of Professional Identity In Health Care Professions:...mentioning
confidence: 99%
See 3 more Smart Citations
“…professional or minoritised groups), we necessarily only capture part of the story. Indeed, there is an increasing chorus of researchers critiquing the lack of diversity reflected in the ‘data’ on professional identities (historically comprising of White, male and medical cultures) and the need for a critical perspective from researchers 2,14,15,17 . One of these absent groups comprises mental health professionals, specifically clinical psychologists, which are the focus of this article.…”
Section: Reviews Of Professional Identity In Health Care Professions:...mentioning
confidence: 99%
“…All texts reported that professional identity was related closely to personal identity, with variations in emphasis, language and description of this relationship. Descriptions ranged from explicitly describing the evolution of professional identity from personal identity, characteristics or experience (2,6,7,8,10,16,17,19,20), the progressive integration or congruence between personal and professional identity (…”
Section: Theme 1: Integration Of Personal and Professional Identitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, clarifying your stance on identity facilitates aligning education practices to support professional identity formation. For example, an individual perspective of identity leads to student‐focused interventions, which might have unintended consequences of leaving the individual to grapple with cultural problems embedded within systems 13 . Alternatively, highlighting socialisation processes places the onus on educators to examine the learning environment as a shaping force on identities.…”
mentioning
confidence: 99%